THE USE OF QUESTION-ANSWER RELATIONSHIP (QAR) STRATEGY TO ENHANCE THE ELEVENTH GRADE STUDENTS’ READING COMPREHENSION - Della Mutiara (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
Students get difficulty in comprehending the words in the reading. The purpose of the research is to find out the effect of using the question-answer relationship (QAR) strategy on the eleventh-grade students’ reading comprehension especially narrative texts. It was conducted on the eleventh-grade students of SMAN 4 Cibinong. Thirty-five students were taken as the sample. The method used in this research was pre-experimental, with one group pre-test post-test research design. The data were collected through reading comprehension pre-test and post-test scores in the form of multiple-choice items. The data were analyzed using the t-test formula. The result showed that the value of t-value was 16.86, while the value of the t-table was 2.03 with the degree of freedom of 34 at the significance level (a) 0.05. Thus, the alternative hypothesis (Ha) of this research was accepted.